Supramolecular macrocycle regulated single-atom MoS2@Co catalysts for enhanced oxygen evolution reaction - Cao, Shuai (2024)
The development of active water oxidation catalysts for water splitting has stimulated considerable interest. Herein, the design and building of single atom Co sites using a supramolecular tailoring strategy are reported, that is, the introduction of pillar[4]arene[1]quinone (P4A1Q) permits mononuclear Co species stereoelectronically assembled on MoS2 matrix to construct an atomically dispersed MoS2@Co catalyst with modulated local electronic structure, definite chemical environment and enhanced oxygen evolution reaction performance. Theoretical calculations indicate that immsobilized single-Co sites exhibit an optimized adsorption capability of oxygen-containing intermediates, endowing the catalyst an excellent electrocatalytic oxygen evolution reaction activity, with a low overpotential of 370 mV at 10 mA cm−2 and a small Tafel slope of 90 mV dec−1. The extendable potential of this strategy to other electrocatalysts such as MoS2@Ni and MoS2@Zn, and other applications such as the hydrogen evolution reaction was also demonstrated. This study affords new insights into the rational design of single metal atom systems with enhanced electrocatalytic performance.